Effects of pre-reproductive maternal enrichment on maternal care, offspring's play behavior and oxytocinergic neurons. (February 2019) - Cutuli, Debora; Berretta, Erica; Caporali, Paola; Sampedro-Piquero, Patricia; De Bartolo, Paola; Laricchiuta, Daniela; Gelfo, Francesca; Pesoli, Matteo; Foti, Francesca; Farioli Vecchioli, Stefano; Petrosini, Laura
Abstract: Potentiating social, cognitive, and sensorimotor stimulations the Environmental Enrichment (EE) increases levels of novelty and complexity experienced by individuals. Growing evidence demonstrates that parental EE experience, even occurring in the pre-reproductive phase, affects behavioral and neural developmental trajectories of the offspring. To discover how the accumulation of early maternal complex experiences may inform and shape the social behavior of the following generation, we examined the effects of pre-reproductive enrichment of dams (post-natal days 21–72) on the play performances of their male and female adolescent offspring. Furthermore, we examined the effects of pre-reproductive enrichment on maternal behavior (during post-partum days 1–10) and male intruder aggression (on post-partum day 11). Since oxytocin modulates maternal care, social bonding, and agonistic behavior, the number of oxytocinergic neurons of the paraventricular (PVN) and supraoptic (SON) nuclei was examined in both dams and offspring. Results revealed that enriched females exhibited higher levels of pup-oriented behaviors, especially Crouching, and initiated pup-retrieval more quickly than standard females after the maternal aggression test. Such behavioral peculiarities were accompanied by increased levels of oxytocinergic neurons in PVN and SON. Moreover, pre-reproductive maternal EE cross-generationally influenced the offspring according to sex. Indeed, male pups born to enriched females exhibited a reduced play fighting associated with a higher number of oxytocinergic neurons in SON in comparison to male pups born to standard-housed females. In conclusion, pre-reproductive EE to the mothers affects their maternal care and has a cross-generational impact on the social behavior of their offspring that do not directly experiences EE. This article is part of the Special Issue entitled "Neurobiology of Environmental Enrichment". Highlights: Pre-reproductive maternal enrichment affects maternal care and pups' social behavior. Pre-reproductive enrichment increases crouching during the first 10 post-partum days. Enriched dams show increased levels of oxytocinergic neurons in hypothalamic nuclei. Male pups from enriched dams exhibit a reduced play fighting. Male pups from enriched dams show high levels of oxytocinergic hypothalamic neurons.